KOMPOSISI JENIS IKAN YANG TERTANGKAP DARI BEBERAPA ALAT TANGKAP DI PERAIRAN MUSI BAGIAN TENGAH, SUMATERA SELATAN (Jurnal Ilmu-ilmu Perikanan dan Budidaya Perairan, 2026)
A study in order to determine the selectivity and productivity of some fishing gears was conducted in the middle part of Musi River Basins from May 1996 to February 1997. Survey was conducted with purposive sampling methods by visiting the fishermen villages, listing the fishing gears and methods as well as identifying of fish species caught. Result showed that 16 types of gears found in locations and they could be classified into 3 groups of very selective (tabung/tube rap), unselective (fortable traps, lift nets, scoop nets, hook and lines, longlines, spears and harpoons) and very unselective (barrier traps, funnel traps, cast nets, gillnets and fish aggregating devices). Based on the fish composition, barrier, funnel, cast net, gillnet and FAD were categorized as productive fishing gears.Keywords : fishing gears, Fish composition, the middle part of Musi River Basins